Diversification and subspecies patterning of the goitered gazelle (Gazella subgutturosa) in Iran - Fadakar, Davoud (Ecol Evol, 2020)
Goitered gazelles, Gazella subgutturosa, exist in arid and semiarid regions of Asia from the Middle to the Far East. Although large populations were present over a vast area until recently, a decline of the population as a result of hunting, poaching, and habitat loss led to the IUCN classification of G. subgutturosa as “vulnerable." We examined genetic diversity, structure, and phylogeny of G. subgutturosa using mitochondrial cytochrome b sequences from 18 geographically distant populations in Iran. The median‐joining network of cyt b haplotypes indicated that three clades of goitered gazelles can be distinguished: a Middle Eastern clade west of the Zagros Mountains (and connected to populations in Turkey and Iraq), a Central Iranian clade (with connection to Azerbaijan), and an Asiatic clade in northeastern Iran (with connection to Turkmenistan, Uzbekistan, and other Asian countries as far as northeastern China and Mongolia). Based on our results, we argue that Iran is the center of diversification of goitered gazelles, due to the presence of large mountain ranges and deserts that lead to the separation of populations. In accordance with previous morphological studies, we identified the Asiatic clade as the subspecies G. s. yarkandensis, and the other two clades as the nominate form G. s. subgutturosa. The new genetic information for goitered gazelles in Iran provides the basis for future national conservation programs of this species.